Cut‐to‐the‐light technique is useful for complete obstruction of a Wallace ureteroileal anastomosis. Issue 2 (3rd February 2023) - Tsuboi, Ichiro; Yokoyama, Shuhei; Nakajima, Hirochika; Yosioka, Saori; Kobayashi, Yusuke; Nagami, Taichi; Ogawa, Kohei; Wada, Koichiro
Abstract : Introduction: Obstruction of a ureteroileal anastomosis after urinary diversion is an unpleasant situation for patients and clinicians alike. Case presentation: A 48‐year‐old man who underwent a radical cystectomy for muscle‐invasive bladder cancer and urinary diversion using the Wallace technique complained of right back pain. Computed tomography showed right hydronephrosis. Cystoscopy via the ileal conduit revealed complete obstruction of the ureteroileal anastomosis. We performed a bilateral approach (antegrade and retrograde) to use the cut‐to‐the‐light technique. A guidewire and 7Fr single J catheter could be inserted. Conclusion: The cut‐to‐the‐light technique was useful for complete obstruction of the ureteroileal anastomosis, the length of which was <1 cm. Herein, we report on the cut‐to‐the‐light technique with a literature review.